Efficacy and satisfaction of preoperative telemedicine evaluation of pediatric urologic patients - Canon, Stephen; Whitt, Jedidiah; Spray, Beverly; Patel, Ashay; Zamilpa, Ismael (Frontiers in Urology, 2022)
Introduction: Minimal data exists on the accuracy of preoperative assessment with telemedicine compared to in-person preoperative evaluation. The aim of the study was to compare the efficacy of telemedicine in a clinic or home setting to an in-person approach for pediatric patients with urologic surgical problems. Methods: Preoperative pediatric urologic telemedicine patients between 5 days and 7 years evaluated at our institution were reviewed between January 2011 and June 2020. Both traditional clinic telemedicine patients (TM) and home telemedicine patients (TMH) were included and compared to an in-person (IP) control cohort. Caregivers were invited to complete a National Research Council (NRC) satisfaction phone survey. Data on demographics, preoperative diagnosis/surgical plan, diagnosis at surgery, and surgical procedure were collected. Results: 96 patients with completed surveys were included in the study (34 TM, 24 TMH, 38 IP). Median age was 10 months TM, 4 months TMH, and 6 months IP. Ethnicity was predominantly non-Hispanic white: 82.4% TM, 91.7% TMH, and 89.5% IP (p=0.413). Preoperative assessment accuracy was equivalent in the three groups with 29/34 (85.3%) TM patients, 22/24 (91.7%) TMH patients, and 35/38 (92.1%) IP patients having an accurate surgical plan (p=0.69). Overall caregiver satisfaction was equivalent (p=0.231). Conclusion: Utilization of telemedicine for pediatric urological surgical planning may be as effective in accuracy and caregiver satisfaction as that of in-person evaluation.